Behavioral and Cultural Control in Supporting Organizational Sustainability - Syahrudin, Muhammad Syahrudin; Amelia Setiawan; Hamfri Djajadikerta (Universitas Trisakti, 2026)
This study closely examines how research on behavioral control and cultural control has developed within management control systems. It also looks at how these two types of control work together to help organizations reach sustainability and the Sustainable Development Goals (SDGs), especially SDG 8 (Decent Work and Economic Growth) and SDG 16 (Peace, Justice, and Strong Institutions). The research uses a Systematic Literature Review (SLR) method based on the PRISMA framework. It analyzes 16 selected articles published between 2000 and 2025 from both international (Scopus-indexed) and national (SINTA-indexed) journals. The findings show that research has moved from focusing mainly on structures and psychology to more value-based, ethical, and sustainability-centered control models. The literature indicates that behavioral control works best when it is part of a strong cultural control system. This allows organizations to align their formal monitoring with shared values, ethical standards, and employee self-regulation. When both types of control are used together, they help improve organizational performance, ethical behavior, employee well-being, and the ability to adapt to digital and sustainability-focused environments. However, the review also points out some challenges, such as being too controlling, cultural mismatch, psychological burnout, and resistance to digital monitoring. This study helps by offering a combined framework that shows how behavioral and cultural control can work well together for sustainable organizational management. It also suggests that future research should consider different contexts, cross-cultural factors, and longer time periods.